2019
DOI: 10.1155/2019/5813549
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Kangxianling Decoction on Expression of TGF-β1/Smads and Extracellular Matrix Deposition

Abstract: Kangxianling (KXL) decoction is a traditional Chinese herbal formulation which has been used to treat early and midterm chronic renal failure. Renal fibrosis is a common characteristic of progressive chronic kidney diseases (CKD). The formation of renal fibrosis is caused by kidney trauma, infection, and immune response. The pathophysiological mechanism of renal fibrosis was mainly due to increased collagen synthesis in the kidney, decreased degradation, and a large amount of extracellular matrix (ECM) deposit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 31 publications
0
8
0
Order By: Relevance
“…e TGF-β mediated Smads signaling pathway is a pivotal mechanism in the development of PF [44]. When TGF-β1 is stimulated, TGF-β1 binds to the type II TGF-β receptor and triggers the autophosphorylation of the type I TGF-β receptor to active Smad2/3, promoting fibroblast proliferation, differentiation, and ECM remodeling [45,46]. In this study, the cell count of total cells, macrophages, neutrophils, and lymphocytes were increased among the rats with PF.…”
Section: Discussionmentioning
confidence: 99%
“…e TGF-β mediated Smads signaling pathway is a pivotal mechanism in the development of PF [44]. When TGF-β1 is stimulated, TGF-β1 binds to the type II TGF-β receptor and triggers the autophosphorylation of the type I TGF-β receptor to active Smad2/3, promoting fibroblast proliferation, differentiation, and ECM remodeling [45,46]. In this study, the cell count of total cells, macrophages, neutrophils, and lymphocytes were increased among the rats with PF.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, many studies have shown that overexpression of Smad7 caused the inhibition of renal inflammation by inhibiting NF- κ B activation [ 56 , 57 ]. Smad7, a negative regulator of TGF- β signaling, is able to compete with Smad3, in order to inhibit the phosphorylation of receptor-activated Smads [ 58 ]. In this regard, it is worth noting the effects of XXD on the TGF- β /Smads in AKI aged mice.…”
Section: Discussionmentioning
confidence: 99%
“…The expression level of α-SMA and collagen I in kidney were assessed in paraffin-embedded kidney sections (4-µm-thick). Immunohistochemical staining was performed as described previously [8,9]. The results were conducted quantitatively by using Image Pro Plus 6.0.-1 system and ten high-power fields (400× magnification) were analyzed separately for each immunohistochemical reaction in renal tissue.…”
Section: Methodsmentioning
confidence: 99%